Awareness and Knowledge of Fintech among Islamic Banking and Finance Students in Pakistan - Hassnian Ali; Mohammad Zaki Zain; Hadia Saqib Hashmi; Muhammad Hassan Abbas; Muhammad Waqas Shahid; Usman Tariq (Islamic Banking and Finance Review, 2018)
Purpose: The paper aims to investigate the level of awareness of Islamic banking and finance students about the concepts and terms frequently used in Fintech. The impact of the demographics of respondents on their level of knowledge about Fintech is also analyzed. Design/methodology/approach: Descriptive statistics are used to analyze the level of awareness and knowledge of students regarding Fintech. Multiple linear regression method is used to analyze the impact of the demographics of respondents on their level of awareness and knowledge about the concepts and terms used in Fintech. Findings: Fintech emerged around the globe and reached its peak in recent years. The students of Islamic banking and finance industry cannot overlook this phenomenon and they need to be aware of this innovative and emerging industry. Originality/Value: This paper draws the attention of academia including students, researchers, pen wielders and also of the practitioners of Islamic finance industry towards the dynamic area of Fintech and its applications that has not received enough attention so far. Thus, academia and industry may adopt an appropriate strategy regarding this issue.